2018
DOI: 10.20882/adicciones.958
|View full text |Cite
|
Sign up to set email alerts
|

Validación psicométrica del POSIT para el cribado del consumo de riesgo de alcohol y otras drogas entre adolescentes

Abstract: Early detection of alcohol and drug abuse among adolescents is decisive not only for rapid referral and intervention in cases of risk, but also as an indicator for use in the evaluation of prevention programs and public policies to reduce consumption. One of the most widely-used screening instruments in the world is the Problem Oriented Screening Instrument for Teenagers (POSIT) (Rahdert, 1991), whose substance use and abuse subscale (POSIT UAS ) is a brief tool of enormous applied potential. However, there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
(39 reference statements)
0
4
0
3
Order By: Relevance
“…The POSIT-UAS subscale was validated in an adolescent population in Spain (Araujo, Golpe, Braña, Varela, & Rial, 2018), obtaining an internal consistency of 0.82. In this study, the internal consistency calculated was 0.84. c) The third block entailed the sociodemographic characteristics of the population such as sex, age, school year and kind of school (public or charter).…”
Section: Questionnairementioning
confidence: 99%
“…The POSIT-UAS subscale was validated in an adolescent population in Spain (Araujo, Golpe, Braña, Varela, & Rial, 2018), obtaining an internal consistency of 0.82. In this study, the internal consistency calculated was 0.84. c) The third block entailed the sociodemographic characteristics of the population such as sex, age, school year and kind of school (public or charter).…”
Section: Questionnairementioning
confidence: 99%
“…Para su empleo en este trabajo, dicha entrevista fue traducida y contra-traducida bajo la supervisión de sus autores originales. La fiabilidad de las distintas escalas diagnósticas fue elevada obteniendo un valor α de Cronbach de ,88 para el diagnóstico de un trastorno por consumo de alcohol; de ,89 para el diagnóstico de un trastorno por consumo de cannabis y de ,92 para el diagnósti-co de un trastorno por consumo de sustancias, siendo estos valores muy similares a los obtenidos en el trabajo de Araujo, Golpe, Braña y Varela (2017).…”
Section: Instrumentounclassified
“…Por último, como indicador complementario de validez de criterio se incluyó la subescala de Uso y Abuso de Sustancias del Problem Oriented Screening Instrument for Teenagers (POSIT UAS ) (Rahdert, 1991), que consta de 17 ítems dicotómicos (sí/no) y que fue validado en el trabajo de Araujo et al (2017), presentando una buena fiabilidad (a de Cronbach de ,82), al igual que unos elevados valores de sensibilidad (94,3%) y especificidad (83,9%).…”
Section: Instrumentounclassified
“…Twenty-eight studies (reported in 37 publications) with 65 720 participants addressed the accuracy of drug use screening instruments. Considerable heterogeneity among studies was present in the populations (eTable 3 in the Supplement), screening instruments (eTable 4 in the Supplement), substances addressed, reference standards, and target conditions.…”
Section: Resultsmentioning
confidence: 99%